α(1)-Adrenoceptors in the lateral septal area modulate food intake behaviour in rats - Scopinho, A A (Nature Publishing Group, 2008)
BACKGROUND AND PURPOSE: Control of food intake is a complex behaviour which involves many interconnected brain structures. The present work assessed if the noradrenergic system in the lateral septum (LS) was involved in the feeding behaviour of rats. EXPERIMENTAL APPROACH: In the first protocol, the food intake of rats was measured. Then non-food-deprived animals received either 100 nL of 21 nmol of noradrenaline or vehicle unilaterally in the LS 10 min after local 10 nmol of WB4101, an α(1)-adrenoceptor antagonist, or vehicle. In the second protocol, different doses of WB4101 (1, 10 or 20 nmol in 100 nL) were microinjected bilaterally into the LS of rats, deprived of food for 18 h and food intake was compared to that of satiated animals. KEY RESULTS: One-sided microinjection of noradrenaline into the LS of normal-fed rats evoked food intake, compared with vehicle-injected control animals, which was significantly reduced by α(1)-adrenoceptor antagonism. In a further investigation, food intake was significantly higher in food-deprived animals, compared to satiated controls. Pretreatment of the LS with WB4101 reduced food intake in only food-deprived animals in a dose-related manner, suggesting that the LS noradrenergic system was involved in the control of food intake. CONCLUSION AND IMPLICATIONS: Activation by local microinjection of noradrenaline of α(1)-adrenoceptors in the LS evoked food intake behaviour in rats. In addition, blockade of the LS α(1)-adrenoceptors inhibited food intake in food-deprived animals, suggesting that the LS noradrenergic system modulated food intake behaviour and satiation.